P148 ROLE OF IL-33-DEPENDENT INNATE IMMUNE RESPONSES IN COLITIS-ASSOCIATED CANCER. (7th February 2019) - De Salvo, Carlo; Lopetuso, Loris; Buela, Kristine-Ann; Goodman, Wendy; Di Martino, Luca; Pizarro, Theresa
Abstract: Background: IBD patients have an increased risk of developing colorectal cancer, however, the immune cells and cytokines that mediate the transition from intestinal inflammation to cancer are poorly understood. Mucosal IL-33 is increased in UC patients, in addition, IL-33 and its receptor, ST2, are expressed in polyps in AOM/DSS models of colitis-associated cancer. Therefore, several studies have implicated IL-33, which is also an important activator of Innate Lymphoid Cells type 2 (ILC2s), in the formation of tumors. Moreover, it has been shown that ecto-5'-nucleotidase (CD73), critical ectoenzyme in purine metabolism which hydrolyzes extracellular AMP to adenosine, is upregulated in cancerous tissues, and an incompetent purine metabolic pathway has been associated with inflammation and inappropriate resolution in numerous inflammatory diseases, including IBD. Methods: In order to induce colitis-associated polyposis, AOM/DSS protocol was performed on 10-wk-old C57BL/6, IL-33KO and ST2KO mice as follow: the carcinogen Azoxymethane (AOM) was injected intraperitoneally on day 0. After two weeks, 3% dextran sodium sulfate (DSS) was administered in drinking water for a week, followed by two weeks of recovery with normal water. DSS administration and recovery was repeated one more time before euthanizing mice for tissue collection and analysis. Results: IL-33 and ST2 mRNA expression and protein concentration in the colon were significantly increased in AOM/DSS treated C57BL/6 mice compared to controls. Moreover, IHC staining revealed an interesting pattern of ST2 positive cells, consistently localized in the interstitial areas of the upper part of the polyps. Interestingly, in IL-33KO and ST2KO mice, survival rate was better and overall polyps number lower than age-matched C57BL/6 WT controls, after AOM/DSS treatment. On the other hand, CD73 and markers of purine metabolism were decreased in full thickness colon of mice lacking IL-33 or ST2 vs. WT controls after treatment with AOM/DSS. Moreover, FACS data on cells isolated from polyps of mice treated with AOM/DSS showed a subpopulation, belonging to the hematopoietic compartment, positive for both ST2 and CD73, that was less represented in mice lacking IL-33 compared to WT, and further FACS analysis on cells from mesenteric lymph node of C57BL/6 mice treated with AOM/DSS, showed a clear CD73 expressing ILC2 cell population. And in fact, ILC2s were considerably decreased in polyps from ST2KO mice compared to WT after AOM/DSS treatment. Conclusion: Taken together our data suggest that IL-33 is critical in the development of colitis-associated colon cancer by contributing in activating pathways associated with purine metabolism and promoting the expansion of type 2 innate lymphoid cells.